PENGARUH MODEL QUANTUM TEACHING BERBASIS MEDIA DIGITAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V - Panjaitan, Zindi Aulia; Tanjung, Darinda Sofia; Ana, Juli; Sipayung , Regina; Silaban, Patri Janson (Universitas Negeri Medan, 2025)
This study aims to determine the This study aims to determine the effect of the Quantum Teaching model on student learning outcomes in Mathematics subjects in Class VA of SD Negeri 067245 Medan Selayang in the 2024/2025 Academic Year. The research method used is an experimental method with a quantitative research type. To obtain the required data, a test instrument of 20 questions and a questionnaire of 25 items were used. The number of research samples was 25 students based on random sampling technique. To find out the initial ability of students, the study conducted a Pretest with an average score of 42.8 which was included in the failed category. The results of the Pretest had an increase from the results of the Posttest given previously with an average student score reaching 84.8 with a very good category. It can be said that the level of success of student learning outcomes using the Quantum Teaching model increased and had a strong effect, as evidenced by the results of the correlation coefficient test calculation obtained r_count ≥ r_table with a result of 0.728 ≥ 0.380. Furthermore, the hypothesis test compares the value of t_count ≥ t_table. The value of t_count = 5.097 while t_table = 1.708. Because t_count ≥ t_table (5.097 ≥ 1.708) then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the Quantum Teaching learning model (X) on student learning outcomes (Y).